A material for simultaneous adsorption of multiple mycotoxins, its preparation method and application in acidic food matrix
By preparing zein/magnetic modified mesoporous quartz sand composite, the existing adsorbents have been solved in the lack of ability to simultaneously remove multiple mycotoxins in corn and the nutritional loss in acidic food matrix, achieving the effect of efficient adsorption and low nutritional loss.
Patent Information
- Application Number
- CN202410825960.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-06-25
AI Technical Summary
The existing adsorbents are ineffective in synchronously and efficiently removing aflatoxin B1, zearalenone and deoxyfusarium ceramol toxins in corn, and there is a problem of nutrient loss when used in acidic food matrix.
Zein/magnetic modified mesoporous quartz sand composite material is used. This material is modified by acid method and magnetically modified, and combined with zein, it is wrapped with magnetically modified quartz sand to form a composite material with high adsorption capacity.
Efficient adsorption of three major mycotoxins in corn under acidic conditions reduces the loss of nutrients during adsorption and improves the performance of adsorbed materials in complex food matrix.
Smart Images

Figure CN118767881B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a multi-mycotoxin simultaneous adsorption material, a preparation method thereof and an application thereof in an acidic food matrix. Background Art
[0002] Corn is the main food crop in my country and the main raw material for feed and breeding. Corn is susceptible to infection by toxin-producing fungi, which produce mycotoxins. The main toxins are aflatoxins (AFT), zearalenone (ZEN) and deoxynivalenol toxin (DON), which are highly mutagenic and carcinogenic. Contaminated corn seriously endangers the life and health of humans and animals. Therefore, the national food safety standard has made strict regulations on the content of aflatoxin B1 (AFB1), zearalenone and deoxynivalenol toxin in corn, with the limit standards of 20ug / kg, 60ug / kg and 1000ug / kg respectively. Since the chemical properties of mycotoxins produced by fungi are relatively stable and are not affected by the deep processing of corn, the simultaneous and efficient removal of these three toxins in corn processing is an important measure to solve the mycotoxin contamination of corn.
[0003] There are currently two main methods for removing mycotoxins, namely, degradation of toxins and adsorption of toxins. Degradation and detoxification involve chemical, biological and physical methods, such as ozone, biodegradation enzymes, ultraviolet light, etc., to convert toxins into low-toxic or non-toxic substances. These methods have good degradation effects, but still face difficulties such as nutrient loss, production of unknown substances, and long reaction time, which need to be overcome. Another feasible method is to bind toxins through adsorbents. Due to its advantages such as low cost, simple operation, and ease of large-scale use, its application has attracted more and more attention. Adsorbents are added to food and adsorb toxins like sponges, and then the toxins are removed by filtration or centrifugation. Therefore, adsorbents are crucial to the process of removing toxins. At present, the adsorbents that are widely studied mainly include activated carbon, kaolin, bentonite, montmorillonite, etc., but the application of these adsorbents also has areas that need to be improved, such as how to simultaneously and quickly adsorb the main toxins in corn such as AFB1, ZEN, and DON; and when the adsorbent is separated from the detoxified food, a large amount of nutrient loss will inevitably occur. Studies have shown that activated carbon is an effective adsorbent, but 4.4 kg of vegetable oil will be lost after 1 kg of activated carbon is treated. How to simultaneously adsorb multiple fungal toxins while reducing the loss of nutrients is a key issue that toxin adsorbents need to solve.
[0004] Corn is the main source of starch. During the starch extraction process from corn, it needs to be soaked in sodium bisulfite. At this time, the acidity of corn pulp is about 5.4. At the same time, the prepared corn starch powder is acidic. How to efficiently and quickly adsorb the three toxins AFB1, ZEN, and DON in complex food matrices during the corn starch production process (acidic conditions) has not been reported so far. Regarding the adsorption of mycotoxins in corn, Zhang Yakun et al. (2021) reported that the composite modified montmorillonite II prepared by octadecyltrimethylammonium chloride had the best adsorption effect on AFB1 and ZEN in sprayed corn husks. When the addition amount was 1%, the adsorption rates of AFB1 and ZEN were 62.60% and 43.38%, respectively. However, this material failed to adsorb the non-polar toxin DON, and its adsorption performance under acidic conditions was not studied. The acid- and hexadecyltrimethylammonium bromide-modified montmorillonite prepared by Mao et al. (2019) showed excellent adsorption capacity for AFB1 and ZEN under both acidic and alkaline conditions compared with the raw montmorillonite. However, the adsorption capacity of all modified montmorillonites for DON was very low because of its poor planarity and inability to enter the interfacial layer of montmorillonite. Summary of the invention
[0005] The present invention provides a zein / magnetically modified mesoporous quartz sand composite material, which is a fungal toxin adsorption material. The preparation method thereof is as follows:
[0006] (1) Preparation of magnetically modified mesoporous quartz sand
[0007] Adding quartz sand to an acid solution, microwave treatment, cooling; centrifuging, washing the precipitate to obtain modified mesoporous quartz sand; adding water to the modified mesoporous quartz sand, ultrasonically dispersing it in a water bath, then adding FeCl3.6H2O and FeSO4.7H2O, adding NH4OH solution in a water bath, stirring until the reaction is completed, performing solid-liquid separation, washing the precipitate, and drying to obtain magnetic modified mesoporous quartz sand;
[0008] (2) Preparation of zein / magnetically modified mesoporous quartz sand composites
[0009] Zein is dissolved in an ethanol solution, ultrasonically dispersed in a water bath, and then stirred in a water bath. Magnetic modified mesoporous quartz sand is added and stirred in a water bath until the reaction is completed. Solid-liquid separation is performed, and the precipitate is dried to obtain a zein / magnetic modified mesoporous quartz sand composite material.
[0010] In the above preparation method, in step (1), the usage ratio of quartz sand to acid solution is selected from 0.5-3:3-7; preferably 1:5, g:mL.
[0011] In the above preparation method, in step (1), the acid in the acid solution consists of hydrochloric acid and acetic acid, wherein the concentration of hydrochloric acid is 0.2-0.7 mol / L, preferably 0.5 mol / L; the concentration of acetic acid is 0.8-1.4 mol / L, preferably 1 mol / L.
[0012] In the above preparation method, in step (1), the microwave treatment conditions are selected from: microwave treatment at 65-95°C for 1-2.5 min; preferably: microwave treatment at 85°C for 1 min; the microwave output power is selected from 500-800W; preferably 600W.
[0013] In the above preparation method, in step (1), the cooling is to place the reaction solution in ice water and quickly cool it to room temperature.
[0014] In the above preparation method, in step (1), the microwave treatment and cooling process can be performed twice in succession to enhance the porosity effect of the material.
[0015] In the above preparation method, in step (1), the centrifugation condition is selected from: centrifugation at 10000-13000 rpm for 8-15 min; preferably: centrifugation at 12000 rpm for 10 min.
[0016] In the above preparation method, in the step (1), the dosage ratio of modified mesoporous quartz sand, water, FeCl3.6H2O, FeSO4.7H2O and NH4OH solution is selected from 6-10:60-100:4-8:2-6:0.5-2; preferably 8:80:6:4:1, g:mL:g:g:mL.
[0017] In the above preparation method, in step (1), the water bath temperature is selected from 70 to 90°C, preferably 80°C.
[0018] In the above preparation method, in step (1), the stirring reaction time is selected from 10 to 30 minutes, preferably 20 minutes.
[0019] In the above preparation method, in step (1), the concentration of the NH4OH solution is selected from 15 to 35%, preferably 25%.
[0020] In the above preparation method, in step (2), the usage ratio of the zein, ethanol solution and magnetically modified mesoporous quartz sand is selected from 0.5-2:8-15:1-3; preferably 1:10:2, g:mL:g.
[0021] In the above preparation method, in step (2), the concentration of the ethanol solution is selected from 65 to 85%, preferably 80%.
[0022] In the above preparation method, in step (2), the water bath temperature is selected from 70 to 90°C, preferably 80°C.
[0023] In the above preparation method, in step (2), the stirring reaction time is selected from 5 to 20 minutes, preferably 10 minutes.
[0024] The invention provides a zein / magnetically modified mesoporous quartz sand composite material prepared by the method.
[0025] The present invention provides the use of the zein / magnetically modified mesoporous quartz sand composite material in the adsorption of mycotoxins, preferably in the adsorption of mycotoxins in an acidic food matrix. The acidic food matrix is preferably corn steep liquor.
[0026] In the above application, the fungal toxin is selected from aflatoxin B1, zearalenone and / or deoxynivalenol.
[0027] The beneficial effects of the present invention are:
[0028] The present invention modifies quartz sand by acid method to change the pore size of quartz sand; thereby making the mesopore size of modified quartz sand more suitable for the adsorption of fungal toxins; at the same time, the present invention also performs magnetic modification on the modified quartz sand so that it can quickly separate solid and liquid to obtain magnetic modified quartz sand. In addition, zein is wrapped with magnetic modified quartz sand to obtain zein / magnetic modified quartz sand composite material, and zein has strong competitive adsorption on fungal toxins in complex food matrices, which can make the fungal toxins in the food matrix adsorbed on the zein membrane, and the toxins diffuse into the pores of the modified quartz sand for adsorption, while the nutrients in the food are blocked outside, reducing the loss of nutrients in the adsorption process, and can prevent nutrient macromolecules and insoluble particles from entering the pores of the adsorption material, thereby improving the adsorption capacity of the adsorption material for fungal toxins in complex food matrices. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The scanning electron microscope images of unmodified magnetic quartz sand (A) and magnetic modified mesoporous quartz sand (B);
[0030] Figure 2 Infrared spectra of unmodified magnetic quartz sand (below) and zein / magnetic modified quartz sand composite material (above);
[0031] Figure 3 N2 adsorption / desorption isotherms of unmodified magnetic quartz sand (a) and zein / magnetic modified mesoporous quartz sand (b);
[0032] Figure 4Magnetic hysteresis loops of unmodified magnetic quartz sand and zein / magnetically modified mesoporous quartz sand. DETAILED DESCRIPTION
[0033] In the present invention, unmodified magnetic quartz sand is prepared by the following method:
[0034] Add 400 mL of ultrapure water to 40 g of natural quartz sand (50 mesh), disperse in 80°C water bath ultrasonically for 10 min, then add 30 g of FeCl3.6H2O and 20 g of FeSO4.7H2O, slowly add 5 mL of NH4OH solution (concentration of 25%) in 80°C water bath, stop when the color of the reactant changes from yellow to black (pH = about 11), stir for 20 min and the reaction is complete. Use a magnet to separate the solid and liquid, wash the precipitate with ultrapure deionized water until it is neutral, and dry at 75°C for 3 h to obtain magnetic quartz sand.
[0035] Other materials used in the present invention, if not otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way.
[0036] Example 1
[0037] 1. Preparation of mycotoxin adsorption materials
[0038] 1. Preparation of magnetically modified mesoporous quartz sand
[0039] 40 g of natural quartz sand (50 mesh) was slowly added to 200 mL of acid solution (hydrochloric acid concentration was 0.5 mol / L, acetic acid concentration was 1 mol / L), microwaved at 85°C (microwave output power was 600 W) for 1 min, put into ice water and quickly cooled to room temperature, then microwaved at 85°C (microwave output power was 600 W) for 1 min, put into ice water and quickly cooled to room temperature, centrifuged at 12000 rpm for 10 min, and repeatedly washed with deionized water until neutral, to obtain modified mesoporous quartz sand;
[0040] Add 400 mL of ultrapure water to 40 g of modified mesoporous quartz sand, disperse in an 80°C water bath for 10 min, then add 30 g of FeCl3.6H2O and 20 g of FeSO4.7H2O, slowly add 5 mL of NH4OH solution (concentration of 25%) in an 80°C water bath, stop when the color of the reactant changes from yellow to black (pH = about 11), and stir for 20 min until the reaction is complete. Use a magnet to separate the solid and liquid, wash the precipitate with ultrapure deionized water until it is neutral, and dry it at 75°C for 3 h to obtain magnetic modified mesoporous quartz sand.
[0041] 2. Preparation of Zein / Magnetic Modified Mesoporous Quartz Sand Composites
[0042] 10 g of zein was added to 100 mL of ethanol solution (concentration of 80%) for dissolution, ultrasonically dispersed in a water bath at 80° C. for 10 min, and then magnetically stirred in a water bath at 80° C. for 10 min. Then 20 g of magnetically modified mesoporous quartz sand was added, and magnetically stirred in a water bath at 80° C. for 10 min. A magnet was used for solid-liquid separation, and the precipitate was continued to be stirred in a water bath at 80° C. until dry to obtain a zein / magnetically modified mesoporous quartz sand composite material.
[0043] 2. Characterization of adsorption materials
[0044] 1. Scanning electron microscope image
[0045] Figure 1 The scanning electron microscope images of unmodified magnetic quartz sand (A) and magnetically modified mesoporous quartz sand (B) are shown. Figure 1 It can be seen that the surface of the unmodified magnetic quartz sand has no obvious pores, and there are many impurities and irregularities. The magnetic quartz sand after acid modification has many depressions, more holes, and the impurities are removed.
[0046] 2. Infrared spectrum
[0047] Figure 2 Infrared spectra of unmodified magnetic quartz sand (below) and zein / magnetically modified mesoporous quartz sand composite (above). Figure 2 It can be seen that the absorption peak of quartz sand modified by acid solution changes from 3427.0cm -1 Move to 3429.0cm -1 , and the absorption peak value becomes weaker. This is because the water originally attached to the magnetic quartz sand is destroyed after being modified by acid; at 828.0cm -1 The characteristic peak at 810.0 cm -1 The characteristic peak of the acid-modified quartz sand changed from sharp to smooth and the miscellaneous peaks disappeared compared with the peaks before modification, which indicates that the impurities were removed after modification. -1The peak at 1530 cm represents the NH deformation vibration and C=O stretching vibration of the amide-I region. -1 The peak at 560-570cm is generated by the NH deformation vibration and CN stretching vibration of the amide II region, which is the characteristic peak of alcohol-soluble protein; -1 The strong infrared spectrum at can be attributed to the stretching vibration of the iron-oxygen bonds of Fe3O4.
[0048] 3. BET characterization
[0049] The nitrogen adsorption-desorption curves of zein / magnetically modified mesoporous quartz sand and unmodified magnetic quartz sand were measured by conventional methods.
[0050] The results of the test are as follows Figure 3 As shown:
[0051] It can be seen from the nitrogen adsorption-desorption curves that both zein / magnetically modified mesoporous quartz sand and unmodified magnetic quartz sand belong to type IV isotherms with obvious H3 hysteresis loops. After the relative pressure P / P0 reaches 0.43, capillary condensation occurs and the nitrogen adsorption-desorption curves do not overlap and hysteresis loops appear, indicating that the two materials have mesoporous structures.
[0052] Table 1 shows the surface area, total pore volume and average pore size of the three materials.
[0053] Table 1 Specific surface area, total pore volume and average pore size of zein / magnetically modified mesoporous quartz sand
[0054]
[0055] It can be seen from Table 1 that compared with the unmodified magnetic quartz sand, the specific surface area of zein / magnetically modified mesoporous quartz sand increased from 56.7941 m 2 / g increased to 92.8179m 2 / g, the specific surface area increased by 63.4%; the pore volume increased from 0.166744cm 3 / g increases to 0.238049cm 3 / g, an increase of 42.7%; the average pore diameter increased from 6.3855nm to 9.6801nm, an increase of 51.6%.
[0056] 4. VSM characterization
[0057] The VSM characterization of zein / magnetically modified mesoporous quartz sand and unmodified magnetic quartz sand was carried out using conventional methods.
[0058] The test results are as follows Figure 4 As shown:
[0059] Figure 4It was shown that both materials have super strong magnetism, the saturation magnetization of unmodified magnetic quartz sand is 1.00emu / g; the saturation magnetization of zein / magnetically modified mesoporous quartz sand is 0.93emu / g. The results show that both adsorbents have super strong magnetism. Therefore, the adsorbents can be easily separated from the reaction mixture by applying an external magnetic field.
[0060] Example 2 Mycotoxin adsorption test
[0061] Preparation of corn steep liquor samples:
[0062] Take corn as sample, pick and clean corn kernels manually, remove foreign matter, mold and broken corn kernels. Weigh 30g corn and soak it in 60mL sodium bisulfite solution (concentration is 1%) at 45℃ for 6 hours, then use tweezers to manually remove corn husk and corn germ. Put the separated endosperm and 120mL distilled water in a wall breaking machine for 1min to prepare corn syrup, which is set aside.
[0063] Description: In the conventional corn starch and protein extraction process, sodium bisulfite soaking is required, and the acidity of the corn pulp is about 5.4 at this time. The present invention adds adsorption materials after soaking and grinding; and directly removes fungal toxins in the corn pulp during the corn starch and protein production process.
[0064] 1. Adsorption performance at different pH
[0065] Add three toxins, AFB1, ZEN, and DON, to the corn slurry, respectively, so that the concentration of AFB1 in each corn slurry is 20μg / kg, ZEN is 60μg / kg, and the concentration of DON is 1000μg / kg. Then adjust the pH value of each corn slurry to 2, 3, 4, and 5, respectively. Add adsorbents [zein / magnetically modified mesoporous quartz sand (adsorbent A), magnetically modified mesoporous quartz sand (adsorbent B), and unmodified magnetic quartz sand (adsorbent C)] to each corn slurry, and the final concentration of the adsorbent is 1mg / g. Oscillate at 180rpm at 25℃ for 4h. After the oscillation ends, separate the corn slurry and the adsorbent material with a magnet, determine the fungal toxin content of the corn slurry, and calculate the adsorption amount.
[0066] The test results are shown in Table 2:
[0067] Table 2 Adsorption amount at different pH (mg / g)
[0068]
[0069] Note: The adsorption amount is the mass of mycotoxins adsorbed per gram of adsorbent (mg / g)
[0070] It can be seen from Table 2 that zein / magnetically modified mesoporous quartz sand has a high adsorption capacity for the three toxins under acidic conditions of pH 2-5.4, indicating that the prepared composite material can efficiently adsorb the three toxins under extremely acidic conditions. The reason for this is that the pore size of the prepared adsorption material matches the spatial size of the fungal toxin molecules, and the pores of the adsorption material can highly adsorb and accommodate fungal toxins, enabling it to have a high adsorption capacity in an extremely acidic environment; at the same time, it maintains a stable adsorption capacity within the pH range of 2-5.4.
[0071] 2. Adsorption performance at different adsorption times
[0072] AFB1, ZEN and DON were added to the corn slurry respectively, so that the concentration of AFB1 in each corn slurry was 20μg / kg, the concentration of ZEN was 60μg / kg, and the concentration of DON was 1000μg / kg. Then the pH value of each corn slurry was adjusted to 2. Adsorbents [zein / magnetically modified mesoporous quartz sand (adsorbent A), magnetically modified mesoporous quartz sand (adsorbent B) and unmodified magnetic quartz sand (adsorbent C)] were added to each corn slurry, and the final concentration of the adsorbent was 1mg / g. Oscillate at 180rpm at 25℃ for 0.5, 1, 2, 4, 6, 8, 12, and 24h respectively. After the oscillation, the corn slurry and the adsorbent material were separated by a magnet, the mycotoxin content of the corn slurry was determined, and the adsorption amount was calculated.
[0073] The test results are shown in Table 3:
[0074] Table 3 Adsorption amount at different adsorption times (mg / g)
[0075]
[0076] Note: The adsorption amount is the mass of mycotoxins adsorbed per gram of adsorbent (mg / g)
[0077] It can be seen from Table 3 that zein / magnetically modified mesoporous quartz sand can efficiently adsorb polar and non-polar fungal toxins AFB1, ZEN and DON, and the maximum adsorption capacity of these three toxins is 19.92 mg / g, 59.83 mg / g and 958.58 mg / g respectively; while the adsorption amount of the three toxins by the magnetically modified mesoporous quartz sand without modified zein is significantly lower than that by the modified zein; the reason is that the addition of zein increases the surface area of the material and increases the adsorption capacity; at the same time, the zein wrapped in the magnetically modified mesoporous quartz sand can prevent the macromolecules of corn pulp such as protein, fat and insoluble small particles from entering the pores of the quartz sand, blocking the pores and affecting the adsorption capacity;
[0078] Compared with unmodified magnetic quartz sand, magnetically modified mesoporous quartz sand has significantly improved adsorption capacity for three toxins, especially for non-polar DON. Unmodified magnetic quartz sand has almost no adsorption capacity, while magnetically modified mesoporous quartz sand can adsorb and remove DON in large quantities.
[0079] 3. Simultaneous adsorption performance of three fungal toxins
[0080] (1) Simultaneous adsorption
[0081] AFB1, ZEN and DON were added to corn slurry with a pH value of 2 at the same time to make the final concentrations of 40 μg / kg, 120 μg / kg and 2000 μg / kg, respectively. Adsorbent (zein / magnetically modified mesoporous quartz) was added with an adsorbent concentration of 1 mg / g. The mixture was shaken at 180 rpm for 12 h at 25 °C. After the shaking, the corn slurry and the adsorbent material were separated by a magnet, the fungal toxin content in the corn slurry was determined, and the adsorption rate was calculated.
[0082] (2) Single adsorption
[0083] AFB1 was added to corn slurry with a pH value of 2 to a final concentration of 40 μg / kg, and an adsorbent (zein / magnetically modified mesoporous quartz) was added with an adsorbent concentration of 1 mg / g. The mixture was shaken at 180 rpm for 12 h at 25°C. After the shaking, the corn slurry and the adsorbent material were separated by a magnet, the AFB1 content in the corn slurry was determined, and the adsorption rate was calculated.
[0084] ZEN was added to corn slurry with a pH value of 2 to a final concentration of 120 μg / kg, and an adsorbent (zein / magnetically modified mesoporous quartz) was added with an adsorbent concentration of 1 mg / g. The mixture was shaken at 180 rpm for 12 h at 25 °C. After the shaking, the corn slurry and the adsorbent material were separated by a magnet, the ZEN content in the corn slurry was determined, and the adsorption rate was calculated.
[0085] DON was added to corn slurry with a pH value of 2 to a final concentration of 2000 μg / kg, and an adsorbent (zein / magnetically modified mesoporous quartz) was added with an adsorbent concentration of 1 mg / g. The mixture was shaken at 180 rpm for 12 h at 25 °C. After the shaking, the corn slurry and the adsorbent were separated by a magnet, the DON content in the corn slurry was determined, and the adsorption rate was calculated.
[0086] The test results are shown in Table 4:
[0087] Table 4 Adsorption rate of three toxins in corn syrup by zein / magnetically modified mesoporous quartz materials
[0088] toxin Simultaneous adsorption Single adsorption AFB1 49.25% 49.20% ZEN 48.45% 48.40% DON 49.12% 48.95%
[0089] It can be seen from Table 4 that the adsorption rate of the three fungal toxins by the zein / magnetically modified mesoporous quartz material in the presence of the three toxins in corn slurry is consistent with the adsorption rate in the presence of only one toxin, indicating that there is no competitive adsorption of the three toxins in the composite material, and the composite material can also have a high adsorption rate for the three toxins when the three toxins are present at the same time.
[0090] 4. Effect of adsorption process on the nutritional components of corn syrup
[0091] Zein / magnetically modified mesoporous quartz sand group: AFB1, ZEN and DON were added to 10g corn slurry (pH 2) to make the final concentrations of 20μg / kg, 60μg / kg and 1000μg / kg, respectively, and adsorbent (zein / magnetically modified mesoporous quartz sand) was added with an adsorbent concentration of 1mg / g. The mixture was shaken at 180rpm for 12h at 25°C. After the shaking, the corn slurry and the adsorption material were separated by a magnet. The corn slurry was collected and freeze-dried. The freeze-dried powder was weighed, and the protein, starch, fat, total polyphenols, flavonoids, AFB1, ZEN and DON contents in the corn slurry were determined. The contents in the blank group below were used as controls to calculate the yield and toxin removal rate.
[0092] Blank group: AFB1, ZEN and DON were added to 10g corn slurry (pH 2) to make the final concentrations of 20μg / kg, 60μg / kg and 1000μg / kg, and oscillated at 180rpm for 12h at 25℃. After oscillation, freeze-dried and weighed the freeze-dried powder. The contents of protein, starch, fat, total polyphenols, flavonoids, and AFB1, ZEN and DON in the corn slurry were determined.
[0093] Activated carbon group: AFB1, ZEN and DON were added to 10g corn slurry (pH 2) to make the final concentrations of 20μg / kg, 60μg / kg and 1000μg / kg, adsorbent (activated carbon) was added, the adsorbent concentration was 1mg / g, and oscillated at 180rpm for 12h at 25℃. After the oscillation, the corn slurry and the adsorbent were separated by magnet, the corn slurry was collected, freeze-dried, and the freeze-dried powder was weighed. The protein, starch, fat, total polyphenols, flavonoids content, and AFB1, ZEN and DON content in the corn slurry were determined. The contents in the blank group above were used as controls to calculate the yield and toxin removal rate.
[0094] The test results are shown in Table 5:
[0095] Table 5 Effect of composite material adsorption of fungal toxins on corn syrup quality
[0096]
[0097]
[0098] As can be seen from Table 5, the use of zein / magnetically modified mesoporous quartz to remove fungal toxins in corn slurry has a high toxin adsorption rate and does not cause the loss of nutrients in corn slurry. However, the use of activated carbon to remove fungal toxins results in a large loss of nutrients in corn slurry and a poor toxin adsorption effect.
[0099] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a zein / magnetically modified mesoporous quartz sand composite material, characterized in that: The steps include: (1) Preparation of magnetically modified mesoporous quartz sand adding quartz sand into the acid solution, subjecting it to microwave treatment, and cooling it; Centrifuge and wash the precipitate to obtain modified mesoporous quartz sand; Add water to the modified mesoporous quartz sand, disperse it by ultrasonic in a water bath, then add FeCl3.6H2O and FeSO4.7H2O, add NH4OH solution in a water bath, stir until the reaction is completed, separate the solid and liquid, wash the precipitate, and dry it to obtain magnetic modified mesoporous quartz sand; (2) Preparation of zein / magnetically modified mesoporous quartz sand composites The zein is dissolved in an ethanol solution, ultrasonically dispersed in a water bath, and then stirred in a water bath, and magnetically modified mesoporous quartz sand is added, stirred in a water bath until the reaction is completed, solid-liquid separation is performed, and the precipitate is dried to obtain a zein / magnetically modified mesoporous quartz sand composite material; In the step (2), the usage ratio of the zein, the ethanol solution and the magnetically modified mesoporous quartz sand is selected from 0.5-2 g: 8-15 mL: 1-3 g; the concentration of the ethanol solution is selected from 65-85%; the water bath temperature is selected from 70-90°C; and the stirring reaction time is selected from 5-20 min.
2. The preparation method according to claim 1, characterized in that: In the step (1), the ratio of quartz sand to acid solution is selected from 0.5-3 g: 3-7 mL.
3. The preparation method according to claim 1, characterized in that: In the step (1), the acid in the acid solution consists of hydrochloric acid and acetic acid, wherein the concentration of the hydrochloric acid is 0.2 to 0.7 mol / L; and the concentration of the acetic acid is 0.8 to 1.4 mol / L.
4. The preparation method according to claim 1, characterized in that: In the step (1), the amount ratio of modified mesoporous quartz sand, water, FeCl3.6H2O, FeSO4.7H2O and NH4OH solution is selected from 6 ~ 10 g: 60 ~ 100 mL: 4 ~ 8 g: 2 ~ 6 g: 0.5 ~ 2 mL.
5. The preparation method according to claim 1, characterized in that: In the step (1), the microwave treatment conditions are selected from: microwave treatment at 65-95°C for 1-2.5 min; microwave output power is selected from 500-800 W; water bath temperature is selected from 70-90°C; stirring reaction time is selected from 10-30 min; and the concentration of NH4OH solution is selected from 15-35%.
6. A zein / magnetically modified mesoporous quartz sand composite material prepared by the method according to any one of claims 1 to 5.
7. Use of the zein / magnetically modified mesoporous quartz sand composite material according to claim 6 in the adsorption of fungal toxins in an acidic food matrix.
8. The use according to claim 7, characterized in that: The fungal toxin is selected from aflatoxin B1, zearalenone and / or deoxynivalenol.
Citation Information
Patent Citations
Preparation method of magnetic mesoporous silicon dioxide adsorbent for removing aflatoxin in edible oil
CN104475011A
Process for removal of mycotoxins from insoluble plant-derived protein
US20180263264A1